Reconstruction of Muhammadiyah's Beliefs and Ideals as a Progressive Islamic Paradigm in the Second Century of Muhammadiyah - Chusnul Chotimah; Yulis Sutiani; Mastora; Heri Rifhan Halili (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
The rapid transformation of global society in the era of digitalization, artificial intelligence, and complex humanitarian challenges requires Islamic organizations to strengthen their ideological foundations while maintaining relevance to contemporary issues. Muhammadiyah, as one of the largest modern Islamic movements in the world, possesses a fundamental ideological document known as Matan Keyakinan dan Cita-cita Hidup Muhammadiyah (MKCH), which contains its theological beliefs, organizational orientation, and social ideals. However, MKCH has often been interpreted merely as a normative and historical document, limiting its potential as a dynamic paradigm for Muhammadiyah’s second century. This study aims to analyze the position of MKCH within Muhammadiyah’s intellectual framework, examine its relationship with the concept of Progressive Islam (Islam Berkemajuan), and formulate a reconstruction model of MKCH as an epistemological-operational paradigm. Employing a qualitative approach with library research and critical content analysis, the study utilizes official Muhammadiyah documents and Scopus-indexed scholarly literature as primary sources. The findings reveal that MKCH encompasses three interrelated dimensions: theological, epistemological, and practical. These dimensions constitute the foundation of Progressive Islam and support the reconstruction of MKCH through the reinterpretation of tawhid as social ethics, the strengthening of tajdid as a continuous renewal mechanism, and the transformation of da‘wah through empowerment and innovation. The study concludes that MKCH functions as an ideological constant that bridges Islamic values with contemporary social, digital, and humanitarian transformations, thereby reinforcing Muhammadiyah’s role as a progressive Islamic movement in its second century.